Weevil resistant sweetpotato through biotechnology. - Ghislain, M. (International Potato Center, 2015)
This flyer summarizes the objectives, achievements and plans of CIP’s work to address the problem of weevils through development of weevil resistant sweetpotato varieties through breeding and biotechnology. It outlines the Bt-RNAi combined gene technology being applied, and the progress made between 2014 and 2015 towards achieving the project objectives.